PERAN DAN TANGGUNG JAWAB HAKIM WASMAT TERKAIT PERLINDUNGAN HAK-HAK NARAPIDANA DALAM LEMBAGA PEMASYARAKATAN - Dwi Afrimetty Timoera (Jurnal Ilmiah Mimbar Demokrasi, 2014)
The purpose of this study was to determine how judges Wasmat role in protecting the rights of prisoners in the prison. The method used is a qualitative approach. The results showed that the Judge Wasmat ineffective in doing their jobs. Look at all them in performing their duties only as a mere formality. The main constraint is; First, they not only served as a Judge Wasmat but also as a judge on the Court. Second, the implementation of the tasks Judge Wasmat only set in the Code of Criminal Procedure, but its existence is not considered important between Attorney and Penitentiary Institutions. Third, the distance from the court to prison far enough. Fourth, lack of adequate facilities so as to make the work Wasmat Judges can not run properly.